Developing a Toolkit for Measuring the Levels of Education Quality Assurance of Higher Education Institutions in Vietnam: Problems and Solutions - Thi Thu Hien, Ta; Huong, Nguyen Thi Thu; Luong, Tran Huu; Cuong, Nguyen Huu; Thuy, Bui Thi Thu; Huy, Nguyen Hoa; Nhung, Trinh Thi; Anh, Nguyen Thi Kim; Phuong, Vu Minh (VNU Journal of Science: Education Research, 2020)
This paper discusses the issues relating to the toolkit for measuring the quality assurance level of higher education institutions, the process of developing and detailing the toolkit for its usage in the self-assessment and external assessment process in compliance with the quality assessment standards for higher education institutions issued by the Ministry of Education and Training. Therefrom, the paper proposes solutions for improving the implementation of the toolkit in quality assurance practices within higher education institutions and supporting assessors, accreditation bodies and government agencies for quality evaluation, monitoring and management.